Effect of Nutritional Flushing Using Long-Term Energy and Protein Supplementation on Growth Performance and Reproductive Parameters of Doyogena Ewes in Ethiopia - Ayele, Asfaw Tesfaye; Asmare, Bimrew; Abiso, Tesfaye; Wamatu, Jane (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
Nutritional flushing has the potential to increase reproduction in small ruminants. Utilization of locally available feed resources is imperative if smallholder farmers are to adopt improved nutritional strategies for flushing sustainably. The current experiment investigated the effect of four isonitrogenous (14.7% crude protein) rations formulated to supply low (Lo-ME) or high (Hi-ME) metabolizable energy based on enset leaf (Ensete ventricosum) and commercial concentrate and the effects on local Doyogena ewes in Ethiopia. The current finding indicated the supplementation of both enset leaf and concentrate enhanced the performance of local ewes.